2014
DOI: 10.1007/s10461-013-0691-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Characterizing Places for the Targeted Control of Heterosexual HIV Transmission in Urban Areas

Abstract: Places with active HIV transmission may serve as key locations for targeted control. In 2008–2009, heterosexual sex partner venues in Baltimore, MD were identified using a three-phase process and characterized by the presence or absence of HIV cases. 1,594 participants aged 18–35 years were enrolled at 87 venues. The study yielded an overall HIV prevalence of 3.7%; 42% of venues had ≥1 case of HIV (i.e., HIV positive venues). In final age-adjusted models, HIV positive venues had 10% more high HIV-risk sexual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Potential high STI-risk sex partner meeting venues were identified using a three-phase, venue-based methodology described previously (20, 21) and based on the Priorities for Local AIDS Control Efforts (PLACE) methodology (22). Briefly, in phase one, multiple sources of information were used to identify specific sex partner meeting venues and high STI-risk areas (i.e., census block groups [CBGs]) where sex partner meeting venues might exist).…”
Section: Methodsmentioning
confidence: 99%
“…Potential high STI-risk sex partner meeting venues were identified using a three-phase, venue-based methodology described previously (20, 21) and based on the Priorities for Local AIDS Control Efforts (PLACE) methodology (22). Briefly, in phase one, multiple sources of information were used to identify specific sex partner meeting venues and high STI-risk areas (i.e., census block groups [CBGs]) where sex partner meeting venues might exist).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research, both qualitative and quantitative, has given considerable attention to venues where people meet sexual partners. Studies, including some in Africa, have mapped and characterised these venues,4 26–29 while others have examined sexual behaviours and HIV seroprevalence of workers and customers at venues for social interaction 2 6 8 11 12. Relatedly, other studies have assessed availability of HIV preventive interventions at venues for social interaction and provided a case for support for venue-based HIV programmes 2 30–32.…”
Section: Introductionmentioning
confidence: 99%
“…We used the Priority Locations for AIDS Control Efforts (PLACE) method, an approach used to prioritize physical locations associated with HIV transmission (ie, hotspots), 14,20 to guide recruitment and enrollment. For MSM, recent studies have shown increasing reports of GSN and social media applications as sex partner meeting venues.…”
Section: Methodsmentioning
confidence: 99%
“…While transgender women who have sex with men also have significant HIV vulnerabilities, they are a distinct population and have called for their own tailored HIV control approaches. 19 We used the Priority Locations for AIDS Control Efforts (PLACE) method, an approach used to prioritize physical locations associated with HIV transmission (ie, hotspots), 14,20 to guide recruitment and enrollment. For MSM, recent studies have shown increasing reports of GSN and social media applications as sex partner meeting venues.…”
Section: Study Population Recruitment and Enrollmentmentioning
confidence: 99%